Bone Angiogenesis and Vascular Niche Remodeling in Stress, Aging, and Diseases - Stucker, Sina; Chen, Junyu; Watt, Fiona E.; Kusumbe, Anjali P. (Frontiers in Cell and Developmental Biology, 2020)
The bone marrow vascular niche microenvironments harbor stem and progenitor cells of various lineages. Bone angiogenesis is distinct and involves tissue-specific signals. The nurturing vascular niches in the bone marrow are complex and heterogenous consisting of distinct vascular and perivascular cell types that provide crucial signals for the maintenance of stem and progenitor cells. Growing evidence suggests that the bone marrow niche is highly sensitive to stress. Aging, inflammation and other stress factors induce changes in bone marrow niche cells and their crosstalk with tissue cells leading to perturbed hematopoiesis, bone angiogenesis and bone formation. Defining vascular niche remodeling under stress conditions will improve our understanding of the bone marrow vascular niche and its role in homeostasis and disease. Therefore, this review provides an overview of the current understanding of the bone marrow vascular niches for blood and bone stem cells and their malfunctions during aging, bone loss diseases, arthritis and metastasis.